2016
DOI: 10.1007/s00704-016-1786-x
|View full text |Cite
|
Sign up to set email alerts
|

The heat goes on—changes in indices of hot extremes in Poland

Abstract: On the basis of temperature observations at 60 meteorological stations in Poland, changes in the indices associated with the presence of extremely high air temperatures were examined. Indices associated with heat waves, such as the number of hot days (T max ≥30°C) in the summer months (June, July, August) and beyond the summer months (May, September), the number of extremely hot days (T max ≥35°C), the duration of the longest hot spell in the year, as well as the number of tropical nights (T min ≤20°C) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
(29 reference statements)
8
38
0
1
Order By: Relevance
“…The study demonstrated the significant increase in summer maximum air temperature in Poland, in agreement with previous research conducted for Central Europe, e.g., [8,26,27,33]. This increase is evident from the positive temporal trend in mean seasonal maximum air temperature (0.4 • C per 10 years, on average) as well as from several indices describing the intensity and spatial extent of extreme temperature events, i.e., number of days with temperature extremes (average increase of 1.2 days per 10 years), changes in the threshold of the 95th summer maximum air temperature percentile (average trend of 0.47 • C per 10 years), changes in temperature surplus (average trend of 1.99 • C per 10 years), total area affected by the extreme and the Extremity Index.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study demonstrated the significant increase in summer maximum air temperature in Poland, in agreement with previous research conducted for Central Europe, e.g., [8,26,27,33]. This increase is evident from the positive temporal trend in mean seasonal maximum air temperature (0.4 • C per 10 years, on average) as well as from several indices describing the intensity and spatial extent of extreme temperature events, i.e., number of days with temperature extremes (average increase of 1.2 days per 10 years), changes in the threshold of the 95th summer maximum air temperature percentile (average trend of 0.47 • C per 10 years), changes in temperature surplus (average trend of 1.99 • C per 10 years), total area affected by the extreme and the Extremity Index.…”
Section: Discussionsupporting
confidence: 91%
“…Thermal conditions in Poland and their variability have become correspondingly a subject of local studies, raising a point of temperature extreme occurrence and principles [25,28], their long-term variability, e.g., [29][30][31][32] or extreme events, i.e., heat waves, e.g., [29,33]. As Poland, due to its location ( Figure 1A), is particularly exposed to weather extremes occurrence, many papers have also been …”
Section: Introductionmentioning
confidence: 99%
“…IPCC 2013 and nationally-cf. Kożuchowski and Żmudzka 2001;Graczyk et al 2017; bold in Table 2 total was very high-239 mm (Cebulak 1992;Munzar and Ondraček 2010;Kundzewicz 2011). Maximum 5-day precipitation total in the studied period was observed most often in July 1997 (five records), then in July 1996 (four records) and three cases during June and July 1980 and during August 2006.…”
Section: Methodsmentioning
confidence: 80%
“…This is expressed primarily by the distinct decreasing trends in water flows observed in the main rivers, the source zones of which are situated in this part of Poland (Tomaszewski 2007;Wrzesiński 2009;Nowak 2018a), and by the lowering of the water levels in the lakes (Ilnicki 1996;Ilnicki, Orłowski 2006a;Orłowski, Ilnicki 2007;Choiński, Ptak 2008;Kędziora 2008;Kowalik et al 2008;Marszelewski, Radomski 2008;Kunz et al 2010;Marszelewski et al 2011;Ptak, Ławniczak 2011;Ilnicki et al 2012a, b;Nowak, Gezella-Nowak 2012;Piasecki, Marszelewski 2013;Piasecki, Skowron 2014;Stachowski et al 2016;Nowak 2018a) and ground water levels (Przybyłek, Nowak 2011a, b;Nowak 2018a). The lowering of the level of surface and ground waters in the study region is also related to climate factors (Kędziora 2008;Przybyłek, Nowak 2011a;Ilnicki et al 2012a, b;Stachowski et al 2016;Nowak 2018a), such as the increase in air temperature observed for many years (Kundzewicz, Matczak 2012;Twardosz, Kossowska-Cezak 2013;Graczyk, Kundzewicz 2014;Graczyk et al 2016;Wibig 2018). Equally important is human activity, such as the meliorations realized in this part of Poland on a large scale since the middle of the 19 th century (Choiński, Ptak 2008;Marszelewski et al 2011;Ptak, Ławniczak 2011;Ilnicki et al 2012a, b) or the excessive uptake of waters for municipal and agricultural purposes …”
Section: Discussionmentioning
confidence: 95%